On the very idea of a recovery model for mental health. Issue 1 (8th November 2010) - Thornton, Tim; Lucas, Peter
Abstract : The recovery model has been put forward as a rival to the biomedical model in mental healthcare. It has also been invoked in debate about public policy for individual and community mental health and the broader goal of social inclusion. But this broader use threatens its status as a genuine model, distinct from others such as the biomedical model. This paper sets out to articulate, although not to defend, a distinct recovery model based on the idea that mental health is an essentially normative or evaluative notion. It also aims to show that, supposing this suggestion were to be followed, the norms informing our notion of recovery would be more appropriately construed as eudaimonic than as hedonic in character.